Vulvovaginitis therapy in pregnant women as a preventative method of the perinatal complications development - О. В. Кравченко (Publishing House TRILIST, 2019)
Disorders of the vaginal biocenosis in pregnant women takes the leading place in the etiology of the main obstetric and perinatal complications. Careful attention to the biocenosis of pregnant woman is also due to the fact that the formation of fetus bacterial communities occurs long before its birth. Purpose of the study. Evaluation of the effectiveness of chlorine-containing antiseptics for vulvovaginal infections during pregnancy as a method for the prevention of perinatal complications. Materials and methods. 62 pregnant women in the second and third trimester of gestation were examined. All patients underwent clinical examination, bacterioscopic and bacteriological study of vaginal secretions. Pregnant women with verified vulvovaginal infection received the dequalinium chloride (Femiclin drug), which was used 1 vaginal tablet daily for 6 days. The efficacy of treatment was evaluated according to clinical data before treatment, on the 3rd and 7th day of observation and according to laboratory tests before and after treatment. Study results and discussion. Bacterioscopic and bacteriological examination of vaginal contents showed dysbiotic disorders of the vaginal flora in 77.4% (48) of pregnant women, in 22.9% (11) patients were diagnosed bacterial vaginosis, in 33.3% (16) candidal colpitis, in 31.3% (15) aerobic vaginitis, in 12.5% (6) trichomonas colpitis. Normocenosis in pregnant women was observed in 22.6% of cases. After therapy with Femiclin clinical symptoms was absent in 45 pregnant women (93.8%). A laboratory test after treatment confirmed the effectiveness of the proposed therapy in the same number of patients (93.8%). Conclusions. Femiclin showed high sensitivity against the main causative agents of vulvovaginal infection: optional anaerobes (94.1%), fungi (93.8%) and microaerophilic microorganisms (93.3%). The high efficacy of the drug in case of a vulvovaginal infection during pregnancy allows to recommend it for widespread use to prevent perinatal complications.